IMPACT OF INNOVATIVENESS ON OPERATIONAL PERFORMANCE OF GOVERNMENT LEVEL COMPANIES (GLCs) IN RURAL PAKISTAN: A MODERATING ROLE OF ORGANIZATIONAL CULTURE - Faisal SULTAN; Sadia SHAIKH; Zeshan ANWAR (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Corporate Entrepreneurship is not a new topic in the field of management however there is a lack of literature on the strategy concerning the eastern side of the world. Therefore, several studies indicated the need of thorough research work on the topic from the eastern side, especially from the context of GLCs working in rural areas as these forms of firms, are not only away from corporate entrepreneurship but are also in need of strategies to deal with competition and external environment. Thus, in order to make the study pragmatically significant, the data has been collected from the top and middle-level managers of GLCs in rural areas of Pakistan. The results of the study indicated that innovativeness is perceived as an effective predictor of CE in GLCs in rural Pakistan. However, moderation of organizational culture is nullifying the perceived impact of innovativeness on the operational performance of the firms.